2015
DOI: 10.1016/j.compag.2015.10.001
|View full text |Cite
|
Sign up to set email alerts
|

An innovative approach to predict the growth in intensive poultry farming

Abstract: General rightsThis document is made available in accordance with publisher policies. Please cite only the published version using the reference above. Full terms of use are available: http://www.bristol.ac.uk/pure/about/ebr-terms Abstract 10Chicken weight provides information about growth and feed conversion of the flock in order to identify 11 deviations from the expected homogeneous growth trend of the birds. This paper proposes a novel method 12 to automatically measure the growth rate of broiler chickens … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(50 citation statements)
references
References 17 publications
2
38
0
3
Order By: Relevance
“…The aim of this study was to find the association between environmental predisposing factors continuously measured and leg disorders, manually scored during the welfare assessment procedure, to develop an automated prediction system to detect those lesions since automated systems have been widely used to monitor the behavior, position and activity (Aydin et al, 2010;Peña Fernández et al, 2015), growth (Fontana et al, 2015), and welfare Fontana et al, 2016) of broiler chickens.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The aim of this study was to find the association between environmental predisposing factors continuously measured and leg disorders, manually scored during the welfare assessment procedure, to develop an automated prediction system to detect those lesions since automated systems have been widely used to monitor the behavior, position and activity (Aydin et al, 2010;Peña Fernández et al, 2015), growth (Fontana et al, 2015), and welfare Fontana et al, 2016) of broiler chickens.…”
Section: Discussionmentioning
confidence: 99%
“…Broilers are the fastest-growing and cheapest sources of animal protein among farmed species; their performance is heavily conditioned by environmental parameters such as indoor air temperature, relative humidity, litter quality and ventilation speed (Fontana et al, 2015). Genetic selection for fast growth is known to be influential on leg disorders (Bassler et al, 2013), but several studies linked them to poor environmental conditions (Knowles et al, 2008;Purswell et al, 2012;Kyvsgaard et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Broiler vocalisations are highly correlated with BW, and sound analysis could be a reliable method of measuring the growth rate of broiler chickens. In an intensive broiler farm, a study showed that with the growth of broiler chickens, the peak frequency of the sounds emitted by broilers decreased clearly during the entire life of the birds (Fontana et al, 2015 and. Furthermore, a model to predict the weight of broilers was built and validated by the peak frequency analysis of the broilers' vocalisations (Fontana et al, 2017).…”
Section: Growth Rate Detectionmentioning
confidence: 99%
“…Based on these analyses, together with the recording of the feed uptake (recorded with the traditional feed weighing system), they developed a model to predict feed intake in broilers, which was highly correlated with pecking sounds. A later study, used peak frequency vocalizations emitted by broiler flocks (analysed using Adobe ® Audition™ CS6) to predict growth, as they found that these vocalizations were inversely proportional to bird age and weight [37]. Based on these finding, the authors suggested that the automatic analysis of peak frequency vocalizations would allow the development of prediction tools and, therefore, would permit health and welfare assessment at the farm level, with potential to be used as an early warning system.…”
Section: Sensorsmentioning
confidence: 99%